Methods and preventive measures for juveniles from committing a felony from an islamic perspective - Karzan Faqikhalil Kareem (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
This research focuses on studying juvenile felony in light of Islamic law. The aim of this research is to clarify the age of juveniles, highlight the concept of juvenile felony, the provisions and penalties from the perspective of Islamic jurisprudence, the treatment of preventive and curative measures, the factors driving them to commit crime. Juvenile felony emerged as a result of multiple factors in the life of juveniles that prompted some of them to commit felonies; Juveniles, when they are young, commit felonies due to the availability of criminal means and the corrupt environment and lack of good education, and the honorable Sharia has taken precautionary and preventive measures to address the spread of felony in society, and therefore it was necessary to confront this phenomenon, and my research is concerned with preventive measures for the causes of juvenile felony, and addressing it through studying it from An Islamic perspective, identifying appropriate ways to treat it, and indicating preventive and curative measures to alleviate it.